Acylation of anisole with long-chain carboxylic acids over wide pore zeolites - Wagholikar, S. G.; Niphadkar, P. S.; Mayadevi, S.; Sivasanker, S. (Applied Catalysis A-General, 2007)
The acylation of anisole with long-chain carboxylic acids (hexanoic, octanoic and decanoic) has been studied over three large pore zeolites-beta (BEA), faujasite (FAU) and mordenite (MOR). The acylation of anisole with the long chain acids produced mainly the ketone (4-methoxy phenyl alkyl ketone) and small amounts of the ester (phenyl alkanoate). The results revealed the reaction to be influenced by the type of zeolite and its Si/Al ratio (acidity) besides the chain length (carbon number) of the carboxylic acid. In the acylation of anisole with hexanoic acid, the activity of the zeolites increased with dealumination as it led to the generation of mesopores that resulted in a decrease in diffusion resistance of the zeolites. The reactivity of the acids in the acylation reaction was found to decrease with increase in the carbon number. The experimental data have been fitted into a pseudo first order kinetic model. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Acylation; Anisole; decanoic acid; hexanoic acid; octanoic acid; zeolites